Sayap Pembaharu & Tradisionalis Islam (Mitos atau realitas?) - H Haikal (Al-Jami'ah Research Centre, 2000)
This study, dealing with reformist and traditionalist wings on Islamic movements in Indonesia, is based on research which among other thorough direct participation in many Islamic discourses held Muhammadiyah and NU, at different places and times. In addition to this, the writer conducted several in depth interviews and discussions with either Muhammadiyah's and NU's activists or leaders. in strengthening this study, this writing also based on intensive literature research using primary and secondary sources. Though both wings have stressed their activities in different fields, however both have same aim, especially as their founders also graduated from ponpes (pondok pesantren). The trend of Muhammadiyah's activities in stimulating education is by founding schools such as Mualimin and Muallimat, which on the whole are located in cities or urban areas. While the trend of NU's activities is by strengthening and modernizing their ponpes, which mostly are located in rural areas. However, as the time passes by, both wings tend to get closer and working hand in hand.